Analysis of Factors Affecting Poor Nutrition in Infants Aged 0-6 Months - Harahap, Maryam Latifah; Suryani, Elvi; Rangkuti, Nur Aliyah; Batubara, Novita Sari; Siregar, Rya Anastasya; Siregar, Ratna Dewi (International Journal of Public Health Excellence (IJPHE), 2022)
Malnutrition (kwashiorkor) is a form of malnutrition. Malnutrition itself can be understood as a nutritional error. It can be in the form of deficiency or excess of nutrients. This research is a case control study. The population in this study were 45 people. Data was collected through medical records and interviews using a questionnaire. Data were analyzed univariately, bivariately using Chi-Square test at 95% confidence level (P<0.05) and multivariate using multiple logistic regression test. The results showed that the results of the statistical test of the knowledge independent variable obtained a Sig value of 0.001 < p: 0.05, family income obtained a Sig value of 0.001 < p: 0.05, exclusive breastfeeding obtained a Sig value of 0.001 < p: 0.05, which means that there is a significant relationship between the independent and dependent variables. The most dominant variable that has the greatest influence on the incidence of malnutrition is knowledge which has the largest Exp (B) value of 112,687 with a regression coefficient (B) of 4.725. The Health Office of South Tapanuli Regency is expected to be able to increase outreach and counseling programs about the importance of nutritional status in infants aged 0-6 months.